(untitled) (Journal of Medical & Health Sciences Review, 2025)
The escalating issue of climate change presents an existential threat to biodiversity around the globe, necessitating advanced methods and techniques of conservation. Indirectly, wildlife conservation contributes greatly to the fight against climate change which further illustrates the variety of ecosystem services and the need for areas rich in diversity. Ecosystem services, like carbon and water regulation, are natural processes that help mitigate the impacts of climate change while adhering to ecological system principles. By looking into in detail one of the case studies, current ecosystem-based adaptation strategies, and future directions, this paper nuances the role of biodiversity conservation in the context of climate change as the core element of the future international environmental policy. This retrospective calls for a change in the optics of the evolution of international ecosystem conservation programs, concerning taking care of wildlife and their habitats as one of the ways how to tackle climate change.